Investigation on a soft grasping gripper based on dielectric elastomer actuators. (1st February 2019) - Pourazadi, S; Bui, Huythong; Menon, C
Abstract: A novel soft grasping gripper which is based on dielectric elastomer actuators (DEAs) is presented in this paper. The gripper presents a self-contained and inherently soft approach for grasping objects. A single actuator membrane based on an acrylic elastomer inflates upon application of high electrical voltages. The actuation deformation of the membrane results in a frictional grasp of an underlying object from multiple angles simultaneously. The gripper comprises of a pressurized chamber sealed by the cylindrical DEA and relies on the friction force between the DEA membrane and the object. Mathematical analyses are carried out to simulate the actuation deformation of the DEA membrane and to estimate the grasping force with 3 cylindrical objects of different sizes. Experimental results validate the analytical analyses and show up to around 20% of membrane actuation deformation and 2N of grasping forces.